Effects of sole and amended agricultural by products on soil fertility and the growth and chemical composition of budded rubber - E. I., Moyin Jesu (Universiti Putra Malaysia Press, 2004)
An experiment was out to determine the effectiveness of sole and amended cocoa husk, oil palm bunch ash with poultry, turkey, rabbit manure and spent grain on budded rubber root stock (grafted bud rubber on a root stock) in the field at Akure in the rainforest zone of Nigeria. There were thirteen organic amendment treatments applied at 6t/ha with 300 kg/ha fertilizer as a reference treatment and a control (no fertilizer; no manure). The treatments were arranged in a randomized complete block (REC) design and replicated three times. The soil organic amendment treatments were also chemically analysed while the parameters recorded for the budded rubber were plant height, leaf number, number of nodes, leaf area, soil and leaf N, PL, K Ca, Mg Soil pH and Organic matter (O.M). The results showed that there were significant increases (P< 0.05) in plant height, leaf area, leaf number, nodes number, soil and leaf N,P,K, Ca, Mg Soil pH and organic matter (OM) of budded rubber under different organic amendment treatments compared to the control treatment. Oil palm bunch ash + poultry manure treatments had the greatest number of leaf nodes. Use of NPK fertilizer, spent grain (sorghum based brewery waste) and control treatments reduced mean leaf node number by 50%, 42% and 92% respectively. The amendment oil palm ash + rabbit manure also increase the mean plant height of budded rubber by 56% and 46% compared to the poultry manure and NPK fertilizer respectively. Oil palm bunch ash and cocoa husk residues increased the soil and leaf K and Mg compared to the spent grain while the turkey manure increased growth of budded rubber, soil and leaf N, P, K, Ca, Mg Soil pH and OM. more than poultry and rabbit.